Filling a Geographical Gap: New Paleoecological Reconstructions From the Desert Southwest, USA - Brunelle, Andrea; Minckley, Thomas A.; Shinker, Jacqueline J.; Heyer, Josh (Frontiers in Earth Science, 2018)
In 1916 the time stamp for quantitative palynology was set with Lennart von Post’s initial paper on pollen analysis and environmental change in the Scandinavian peat bogs. His subsequent work and reviews provided us with a map of the known palynological world into the 1930s. This map had, and to this day still has, many substantial holes of knowledge. In particular, environmental reconstruction in arid lands remain much less known, largely due to the paucity of depositional environments in these areas as well as challenges with preservation in regions either uniformly dry or subjected to strong wet/dry cycles. In over a decade of work we have examined linkages between wetland development and episodes of wet and arid conditions. Desert wetland or ciénegas are groundwater fed systems that appear sensitive to changes in groundwater recharge. These systems appear to “grow” during times of wet periods potentially associated with greater El Niño activity, suggesting an important linkage to winter precipitation amounts and frequency. Preservation of pollen is also important, as episodes of aridity can be identified as times of poor pollen preservation and quantities. We assess modern El Niño events, as analogs of past conditions, to provide context on the atmospheric controls for delivery of moisture into the desert southwest during winter. This analysis demonstrates that the anomalous and persistent moisture delivered into the region during El Niño events allow for the growth of ciénegas, preservation of pollen and the production of fuels necessary to support an active fire regime. This paper examines sites from the American Deserts from the US/Mexico Border (hereinafter "southwestern deserts") and presents findings and new approaches that embody the spirit of investigation initiated by von Post’s original work in paleoenvironmental research.